Molecular Mechanisms Underlying Root Nodule Formation and Activity - Katarzyna Nuc; Przemysław Olejnik (Agronomy, 2025)
Symbiotic interactions between legumes and a group of soil bacteria, known as rhizobia, lead to the formation of a specialized organs called root nodules. Inside them, atmospheric nitrogen (N2) is fixed by bacteria and reduced to forms available to plants, catalyzed by the nitrogenase enzyme complex. The development of a symbiotic relationship between legumes and nodule bacteria is a multi-stage, precisely regulated process, characterized by a high specificity of partner selection. Nodulation involves the enhanced expression of certain plant genes, referred to as early- and late-nodulin genes. Many nodulin genes encode hydroxyproline-rich glycoproteins (HRGPs) and proline-rich proteins (PRPs) which are involved in various processes, including infection thread formation, cell signaling, and defense responses, thereby affecting nodule formation and function. Cyclophilins (CyPs) belong to a family of proteins with peptidyl-prolyl cis–trans isomerase activity. Proteins with cyclophilin domain can be found in the cytoplasm, endoplasmic reticulum, nucleus, chloroplast, and mitochondrion. They are involved in various processes, such as protein folding, cellular signaling, mRNA maturation, and response to biotic and abiotic stress. In this review, we aim to summarize the molecular processes involved in the development of symbiosis and highlight the potential role of cyclophilins (peptidyl-prolyl cis-trans isomerases) in this process.